Heritage-led regeneration in the UK. Preserving historic values or masking commodification? A reflection on the case of King’s Cross, London - Chatzi Rodopoulou, Theodora (International Planning History Society Proceedings, 2016)
The rise and fall of industrialisation brought major upheavals on the social, spatial and economic fabric of historic cities, leaving many of them in the late 1970’s in a state of despair. Since the early 1990’s heritage-led regeneration has progressively become an important tool for the revitalisation of urban areas.This revitalisation though, especially when carried out by commercial developers, albeit its positive economic outcome, is not without side effects. This paper aspires to explore how heritage led-regeneration fits in the current 21st century plans for physical, social and economic restructuring of post-industrial historic megacities, like London. Drawing from King’s Cross paradigm, one of the most recent and massive cases of heritage-led regeneration realised in the UK, we will attempt to reflect on the gains and losses of the process, in terms of preservation and resilience of historic, spatial and social values of the area. This reflection will contribute to the evolving discourse on the changing role of heritage in the 21st century prevailing socio-economic system. Focus is cast on the case of King’s Cross, an epitome of industrialisation ‘s life-death and resurrection circle. Once a vibrant transport hub and commercial centre the heart of the first industrial nation’s capital, the area deteriorated, becoming in the 1980’s home of prostitutes and drug dealers. After several proposals, in 2006 an ambitious heritage-led redevelopment project has started which promises the total makeover of the deprived site. In 2011 the first phase of the project was completed. On the first part of the paper, by means of literature review we will present the historic evolution of King’s Cross area from the 19th century to the early 2000’s, highlighting its core historic, spatial and social values. On the second part, we will present the current state of the project and the vision for its future, enriching the literature review methodology by adding material collected from field research. On the second part, using the same method as well as material collected from field research, we will present the current state of the project and the vision for its future. The third part presents the reflection of several stakeholders involved with the scheme, including its developer, architect and users. This is a product of the qualitative research on the subject conducted by the author in July 2015. On the fourth part we will reflect on the outcome of the project, discussing the resilience of King’s Cross industrial heritage after its redevelopment. The paper will conclude with highlighting the underlying implications of heritage led regeneration in the social, spatial and economic fabric of today’s historic city.